A longitudinal study investigating trajectories of sensitivity to threat over time and their association with alpha asymmetry among children and adolescents - Taylor Heffer; Teena Willoughby (Developmental Cognitive Neuroscience, 2020)
Research has yet to investigate trajectories of sensitivity to threat across childhood and adolescence. Further, neural associations of these trajectories remain unknown. The current 3-year study used a latent class growth curve analysis to investigate whether there were distinct trajectories of sensitivity to threat among children and adolescents over time (N = 363; age range at Time 1 = 8–14). We also examined whether alpha asymmetry (a neural index of motivational tendencies) was associated with the different trajectories. Results revealed three distinct trajectory groups (1) high-stable sensitivity to threat, (2) moderate-increasing sensitivity to threat and (3) low-stable sensitivity to threat. The high-stable sensitivity to threat group had greater right frontal asymmetry activation (i.e., greater neural avoidance motivation) than the other two groups. Additionally, females, those with higher parental education, and individuals with more advanced pubertal development (but not age) had greater odds of being part of the high-stable sensitivity to threat group compared to the other groups. Of interest, puberty rather than age may be an important indicator of heightened sensitivity to threat.